Astragalus ladakhense (Galegeae, Leguminosae): a new synonym of Astragalus rhizanthus - Chaudhary, Lal Babu (Phytotaxa, 2018)
The characters of A. ladakhense fall within the range of variation of a quite variable species, A. rhizanthus, and thus the former is reduced to synonymy under the latter.